2-[4-(4-Methoxyphenyl)-5-(2-pyridyl)-4H-1,2,4-triazol-3-yl]phenol - Mei-An Zhu; Zhao-Di Liu; Shu-Ping Zhang; Ying Wei; Si-Chang Shao (Acta Crystallographica Section E, 2009)
In the title compound, C20H16N4O2, the benzene rings of the 2-hydroxyphenyl and 4-methoxylphenyl groups form dihedral angles of 64.02 (8) and 77.39 (7)°, respectively, with the mean plane of the triazole ring. The dihedral angle between the triazole ring mean plane and the pyridyl ring is 9.61 (8)°. In the crystal, intermolecular N—H...O hydrogen bonds link the molecules into zigzag chains propagating in [010].